Utilizing alkali-activated materials as ordinary Portland cement replacement to study the bond performance of fiber-reinforced polymer bars in seawater sea-sand concrete. Issue 5 (April 2022) - Cao, Ruiming; Zhang, Bai; Wang, Luming; Ding, Jianming; Chen, Xianhua
Alkali-activated materials (AAMs) are considered an eco-friendly alternative to ordinary Portland cement (OPC) for mitigating greenhouse-gas emissions and enabling efficient waste recycling. In this paper, an innovative seawater sea-sand concrete (SWSSC), that is, seawater sea-sand alkali-activated concrete (SWSSAAC), was developed using AAMs instead of OPC to explore the application of marine resources and to improve the durability of conventional SWSSC structures. Then, three types of fiber-reinforced polymer (FRP) bars, that is, basalt-FRP, glass-FRP, and carbon-FRP bars, were selected to investigate their bond behavior with SWSSAAC at different alkaline dosages (3%, 4%, and 6% Na2 O contents). The experimental results manifested that the utilization of the alkali-activated binders can increase the splitting tensile strength ( f t ) of the concrete due to the denser microstructures of AAMs than OPC pastes. This improved characteristic was helpful in enhancing the bond performance of FRP bars, especially the slope of bond-slip curves in the ascending section (i.e., bond stiffness). Approximately three times enhancement in terms of the initial bond rigidity was achieved with SWSSAAC compared to SWSSC at the same concrete strength. Furthermore, compared with the BFRP and GFRP bars, the specimens reinforced with the CFRP bars experienced higher bond strength and bond rigidity due to their relatively high tensile strength and elastic modulus. Additionally, significant improvements in initial bond stiffness and bond strength were also observed as the alkaline contents (i.e., concrete strength) of the SWSSAAC were aggrandized, demonstrating the integration of the FRP bars and SWSSAAC is achievable, which contributes to an innovative channel for the development of SWSSC pavements or structures.